2017
DOI: 10.1007/s40279-017-0759-2
|View full text |Cite
|
Sign up to set email alerts
|

Selected In-Season Nutritional Strategies to Enhance Recovery for Team Sport Athletes: A Practical Overview

Abstract: Team sport athletes face a variety of nutritional challenges related to recovery during the competitive season. The purpose of this article is to review nutrition strategies related to muscle regeneration, glycogen restoration, fatigue, physical and immune health, and preparation for subsequent training bouts and competitions. Given the limited opportunities to recover between training bouts and games throughout the competitive season, athletes must be deliberate in their recovery strategy. Foundational compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(98 citation statements)
references
References 209 publications
4
86
0
8
Order By: Relevance
“…A diet rich in fresh fruit and vegetables, wholegrains, legumes, and sprouts as well as seeds is an effective and safe way to meet the antioxidant needs of physically active people [14]. It has been confirmed that satisfying the increased nutritional needs, also in the field of antioxidants, accelerates muscle regeneration processes and glycogen resynthesis, counteracting fatigue and increasing immunity, while improving the efficiency of preparation for subsequent training and competitions [23,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A diet rich in fresh fruit and vegetables, wholegrains, legumes, and sprouts as well as seeds is an effective and safe way to meet the antioxidant needs of physically active people [14]. It has been confirmed that satisfying the increased nutritional needs, also in the field of antioxidants, accelerates muscle regeneration processes and glycogen resynthesis, counteracting fatigue and increasing immunity, while improving the efficiency of preparation for subsequent training and competitions [23,31].…”
Section: Discussionmentioning
confidence: 99%
“…The cited nutritional model emphasizes the special importance of water and other unsweetened beverages for the effective regulation of water and electrolyte balance, as well as vegetables and fruits (products with low and medium glycaemic index, rich in dietary fibre, potassium, magnesium, group B vitamins and antioxidants) for restoring antioxidant status and acid-base balance of the body under physical stress [5,19,23,32,39,42,49]. Incorrect nutritional choices and an unbalanced diet reduce exercise capacity, both indirectly (through negative impact on health and body composition) and directly (via improper nutritional preparation for exercise, improper hydration and weaker post-workout regeneration), and in combination with high intensity training, accelerate the development overtraining syndrome [19,30,39,42].…”
Section: Introductionmentioning
confidence: 99%
“…En la actualidad se está estudiando la adición de curcumina y bromelina a las bebidas de recuperación por su efecto en la reducción de la inflamación postejercicio (19) . De acuerdo con Jeukendrup, las necesidades nutricionales deben ser personalizadas y ajustadas en cada paciente y periodizadas de acuerdo con el plan de entrenamiento (20) .…”
Section: Medidas Nutricionales Para Mantener El Balance Energéticounclassified
“…De esta forma, cuando el entrenamiento y la recuperación se equilibran de manera apropiada, se producen adaptaciones fisiológicas positivas (Nieman & Mitmesser, 2017). Sin embargo, el deportista se enfrenta a múltiples variables que pueden influir en su recuperación, como nutrición (Beck, Thomson, Swift, & von (Nédélec et al, 2015), cambios de zona horaria (Simmons et al, 2015) y/o elevadas cargas de entrenamiento/competición (Heaton et al, 2017).…”
Section: Introductionunclassified